Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Pore-expanded core-shell adsorbent for high Cu(II) adsorption: Performance and DFT mechanism - Yintao Li; Jianwen Wei; Linlin Geng; Dongling Zhao; Xiaobin Zhou (Journal of Water Process Engineering, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Cyclic performance of dual stage energy dissipation joints for connecting CFST column and exterior wide-flat beam - Mingyang Wei; Linlin Song; Jianhua Zhang; Cheav Por Chea; Yan Geng; Xueming Zhang; Dianwei Gao; Zhicheng Liu (Engineering Structures, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

A Study on Energy Loss and Transient Flow Characteristics of a Large Volute Centrifugal Pump During Power-Off Process Under Cavitation Conditions - Qingzhao Pang; Desheng Zhang; Gang Yang; Xi Shen; Qiang Pan; Linlin Geng; Qinghui Lu (Journal of Marine Science and Engineering, 2025)
A novel pumped storage system using centrifugal pumps to transfer water between reservoirs in coastal hydropower plants has significantly mitigated grid instability. However, frequent start–stop operations of large vertical centrifugal pumps, which serve as the core equipment, severely affect the operational stability of these systems. In this study, the intrinsic connection between the cavitating flow field and irreversible losses during the process was analyzed using the entropy production theory. The time–frequency characteristics of pressure pulsation in pump were analyzed by using the continuous wavelet transform. The results indicate that with the reduction in the flow rate and rotational speed, the sheet cavitation at the impeller inlet rapidly weakens until it vanishes. The cavity cavitation within the draft tube commences to emerge in the turbine mode. Separation vortices are formed due to the mismatch in the flow angle at the impeller outlet. These vortices induce local cavitation, causing both a rapid energy loss increase and high-amplitude, low-frequency pressure pulsations. During transient processes, flow instabilities induce high-amplitude, low-frequency pressure pulsations within the stay vane region, with maximum amplitude attained during runaway condition. The research results provide a theoretical foundation for the stable operation of centrifugal pumps.

Engineered ionic liquid-covalent organic framework composites for high-capacity CO₂ capture: Mechanism insights and process optimization - Shuting Zhang; Jianwen Wei; Xuequan Zou; Linlin Geng; Xiaobin Zhou (Journal of Environmental Chemical Engineering, 2025)

Uranium immobilization by Brevundimonas vesicularis LWG1: A synergistic approach via biomineralization, biosorption, and bioreduction - Yanru Liang; Linlin Wang; Panpan Gao; Zichu Qiu; Zemin Qin; Risheng Xu; Yue Li; Wenjuan Shuai; Jimin Li; Xueqing Geng; Hailiang Dong; Yuheng Wang (Journal of Hazardous Materials, 2025)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

Dust removal process of the multi-filter cartridges and its optimization measures for coal dust pollution: Experimental and numerical investigations - Geng Fan; Li Linlin; Huang Ruoxi; Li Shihang; Shi Wentao; Chang Binbin; Peng Zhengbiao; Xia Yuyang (Journal of Environmental Chemical Engineering, 2025)

A novel flow control method suppressing tip leakage vortex of a hydrofoil applied for ducted devices - Fadong Gu; Lei Shi; Xi Shen; Guangjian Zhang; Linlin Geng; Desheng Zhang; B.P.M. (Bart) van Esch (Ocean Engineering, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Machine learning reveals the selection pressure exerted by nonantibiotic pharmaceuticals at environmentally relevant concentrations on antibiotic resistance genotypes - Shaojing Sun; Yan Sun; Jialu Geng; Linlin Geng; Fan Meng; Qing Wang; Hong Qi (Journal of Environmental Management, 2024)

Long-Term Effects of Ecological Restoration Projects on Ecosystem Services and Their Spatial Interactions: A Case Study of Hainan Tropical Forest Park in China - Jiahui Zhong; Linlin Cui; Zhiyin Deng; Yong Zhang; Jie Lin; Geng Guo; Xiang Zhang (Environmental Management, 2024)

Adsorption of high-temperature CO2 by Ca2+/Na+-doped lithium orthosilicate: characterization, kinetics, and recycle - Dongling Zhao; Linlin Geng; Yanfei Jia; Jianwen Wei; Xiaobin Zhou; Lei Liao (Environmental Science and Pollution Research, 2024)

GhFB15 is an F-box protein that modulates the response to salinity by regulating flavonoid biosynthesis - Zhao Geng; Haikuan Dou; Jianguang Liu; Guiyuan Zhao; Zetong An; Linlin Liu; Ning Zhao; Hanshuang Zhang; Yongqiang Wang (Plant Science, 2024)

Dynamic behaviors of cavitation bubbles near biomimetic surfaces: A numerical study - Hongbo Shi; Hang Zhang; Linlin Geng; Sen Qu; Xikun Wang; Petr A. Nikrityuk (Ocean Engineering, 2024)

Li-intercalation chemistry of few-layer borophene with ultrahigh capacity and fast kinetics - Linlin Guo; Huili Wang; Zhonghan Wu; Xinru Yang; Ruoxuan Ma; Yanfang Hu; Geng Li; Dongjie Shi; Wei Xie; Wei Zhang; Fujun Lan; Limin Zhou; et al. (Chemical Engineering Journal, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Accumulation and speciation of arsenic in Eisenia fetida in sodium arsenite spiked soils - A dynamic interaction between soil and earthworms - Weiqin Xing; Hongpei Geng; Yali Wang; Linlin Zhao; Yongqiang Yang; Yale Wang; Shuhang Tian; Yongxin Cao; Zhe Zhang; Liping Li (Chemosphere, 2023)

Responses and tolerance mechanisms of microalgae to heavy metal stress: A review - Xinfeng Xiao; Wenfang Li; Meng Jin; Linlin Zhang; Liguo Qin; Weiwei Geng (Marine Environmental Research, 2023)

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

Identification and Characterization of the Homeobox Gene Family in Fusarium pseudograminearum Reveal Their Roles in Pathogenicity - Yuming Ma; Jingya Zhao; Wenbo Chen; Xuejing Geng; Tianli He; Shengli Ding; Bingjian Sun; Honglian Li; Linlin Chen (Biochemical Genetics, 2022)

Effectiveness of Selenium on Chondrocyte Glycoprotein Glycosylation Which Play Important Roles in the Pathogenesis of an Endemic Osteoarthritis, Kashin–Beck Disease - Sen Wang; Lingling Geng; Guanghui Zhao; Peilin Meng; Linlin Yuan; Xiong Guo (Biological Trace Element Research, 2022)

Large-Eddy Simulation of Cavitating Tip Leakage Vortex Structures and Dynamics around a NACA0009 Hydrofoil - Linlin Geng; Desheng Zhang; Jian Chen; Xavier Escaler (Journal of Marine Science and Engineering, 2021)
The tip leakage vortex (TLV) has aroused great concern for turbomachine performance, stability and noise generation as well as cavitation erosion. To better understand structures and dynamics of the TLV, large-eddy simulation (LES) is coupled with a homogeneous cavitation model to simulate the cavitation flow around a NACA0009 hydrofoil with a given clearance. The numerical results are validated by comparisons with experimental measurements. The results demonstrate that the present LES can well predict the mean behavior of the TLV. By visualizing the mean streamlines and mean streamwise vorticity, it shows that the TLV dominates the end-wall vortex structures, and that the generation and evolution of the other vortices are found to be closely related to the development of the TLV. In addition, as the TLV moves downstream, it undergoes an interesting progression, i.e., the vortex core radius keeps increasing and the axial velocity of vortex center experiences a conversion from jet-like profile to wake-like profile.

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Composites ZSM-5/KIT-6 Synthesized Via Assembly Modification Procedure and Mechanical Grinding Procedure, Respectively, and Their Application to CO2 Adsorption - Zhifeng Lin; Jianwen Wei; Linlin Geng; Dejun Mei; Lei Liao (Water, Air, & Soil Pollution, 2017)

Bagasse Activated Carbon with TETA/TEPA Modification and Adsorption Properties of CO2 - Jianwen Wei; Zhifeng Lin; Zeyu He; Linlin Geng; Lei Liao (Water, Air, & Soil Pollution, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Identification of Novel MicroRNA Signatures Linked to Experimental Autoimmune Myasthenia Gravis Pathogenesis: Down-Regulated miR-145 Promotes Pathogenetic Th17 Cell Response - Jiao Wang; Shuangshuang Zheng; Ning Xin; Changxin Dou; Linlin Fu; Xiuying Zhang; Jing Chen; Yanyan Zhang; Deqin Geng; Chenghua Xiao; Guiyun Cui; Xia Shen; et al. (Journal of Neuroimmune Pharmacology, 2013)

Growth inhibition induced by transforming growth factor-β1 in human oral squamous cell carcinoma - Xiumei Wang; Wenjing Sun; Jing Bai; Linlin Ma; Yang Yu; Jingshu Geng; Jiping Qi; Zhongcheng Shi; Songbin Fu (Molecular Biology Reports, 2009)